2018
DOI: 10.1007/s10461-018-2212-4
|View full text |Cite
|
Sign up to set email alerts
|

Sexual Agreements: A Scoping Review of Measurement, Prevalence and Links to Health Outcomes

Abstract: A sexual agreement is a mutual understanding between two partners regarding sexual and relational behaviors both within and outside of their relationship. Sexual agreements have been central to research and programming efforts around HIV prevention, primarily for male couples. A comprehensive scoping review of the primary literature on sexual agreements, including negotiated safety, was performed to identify what is known about sexual agreements among couples (n = 66). Results indicate a wide range of prevalen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 75 publications
1
23
0
Order By: Relevance
“…This construct is closely related to sexual agreements and breaks within sexual agreements. Our study builds upon previous literature, indicating that breaks within sexual agreements widely vary, however, reasons for breaks and consequences for breaks are less known (Rios-Spicer et al, 2019). For YGBM in our study, breaking a sexual agreement may constitute in ending a relationship.…”
Section: Discussionsupporting
confidence: 78%
“…This construct is closely related to sexual agreements and breaks within sexual agreements. Our study builds upon previous literature, indicating that breaks within sexual agreements widely vary, however, reasons for breaks and consequences for breaks are less known (Rios-Spicer et al, 2019). For YGBM in our study, breaking a sexual agreement may constitute in ending a relationship.…”
Section: Discussionsupporting
confidence: 78%
“…Hurdle models are uniquely suited to detecting this kind of process because they separate out the prediction of the mere occurrence of risk (the binary component of the model) and the prediction of amount or frequency of risky among those who are risky (Hu et al, 2011). Previous research has found that monogamous men report fewer instances of CAS with casual partners compared to single and non-monogamous men (Mitchell et al, 2012;Spicer et al, 2019;; however, these studies examined overall frequencies. These results reveal that while monogamous men may be at lower risk of HIV transmission overall, those who do experience risk are in urgent need of prevention.…”
Section: Discussionmentioning
confidence: 99%
“…This gap in the literature is important because research from the past decade has indicated that sexual agreements -the rules or boundaries couples establish related to sex with partners outside their relationship -are a consistent predictor of sexual behavior with casual partners and drug use. Men in relationships in which explicit agreements around monogamy have been formed -where sex with casual partners is prohibited -are less likely to have sex with casual partners compared to those in non-monogamous relationships (Parsons, Starks, et al, 2013;Spicer et al, 2019;. They are also less likely to use club drugs and marijuana compared to those in non-monogamous relationships Parsons & Starks, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Though unprotected sex with concurrent partners remains the primary mode of HIV acquisition in heterosexual CNC in Africa, couples lack evidence-based pragmatic, communication and action-focused strategies to aid in their decision-making to protect their marriages from HIV. Our ‘Strengthening Our Vows’ approach aims to incorporate this combinative strategy with CVCT, an already proven, cost-effective strategy and adapts strategies previously used to provide a platform for couples to discuss concurrent partnerships and HIV prevention [ 75 , 76 ].…”
Section: Discussionmentioning
confidence: 99%
“…Studies on sexual agreements with heterosexual couples are more limited and mostly assess feasibility of sexual agreements, self-reported monogamy agreements, or perceptions of western providers about agreements [ 105 , 106 ]. In a comprehensive scoping review of the primary literature on sexual agreements, including negotiated safety, Rios-Spicer and colleagues identified several knowledge gaps including the need to expand sexual agreements research beyond MSM populations and the need to better understand agreement breaks and break disclosure [ 75 ].…”
Section: Discussionmentioning
confidence: 99%